Vulcanization for reinforcement of rubber - Ikeda, Y; Miyaji, K; Ohashi, T; Nakajima, T; Junkong, P (Rubber Chemistry and Technology, 95(2): 161-174., 2022)
Sulfur cross-linking reagents play critical roles not only in cross-linking rubber chains but also in controlling network morphology for reinforcement of rubber. Zinc oxide (ZnO) is clearly discovered as the main component for both roles. Especially, the importance of network inhomogeneity, which is significantly governed by the dispersion of ZnO particles, is emphasized for reinforcing rubber materials. Specifically, the formation of network domains and their continuous structures is discussed by combining the mechanical properties of the vulcanizates from the viewpoint of the reinforcement effect of rubber. Two continuous structures of network domains are termed as the network-domain cluster and network-domain network, which are observed by atomic force microscopy. The ZnO particles play a role as template for the formation of the continuous structures of network domains. The findings provide us with a practical hint for producing high-performance rubber materials.
Keywords: Vulcanization; Reinforcement